Can Genetic Risk Information Enhance Motivation for Smoking Cessation? An Analogue Study. - Wright, Alison J.; French, David P.; Weinman, John (Health Psychology, 2006)
Protection motivation theory and the extended parallel processing model are used to predict the motivational impact of information regarding a genetic susceptibility to heart disease. One hundred ninety-eight smokers read 1 of 3 vignettes: gene positive, gene negative, or standard smoking risk information. Analyses examined whether the impact of type of risk information was moderated by smokers' self-efficacy (SE) levels. Key outcomes were intention to quit and intention to attend an information session about quitting. There were significant main effects of SE and of receiving gene-positive risk information on intentions to quit. There was a significant Risk × SE interaction on intentions to attend an information session. SE was not associated with intentions to attend the information session for smokers in the gene-positive group. Intentions to attend the session were negatively associated with SE for smokers in the lower risk groups. Implications for using genetic risk information to motivate smoking cessation are discussed. Reprinted by permission of the publisher.